Decolonizing Through Integration: Australia's Off-Shore Island Territories - Roger Wettenhall (Island Studies Journal, 2016)
Australia’s three small off-shore island territories – Norfolk Island in the Pacific Ocean and Christmas Island and the Cocos (Keeling) Islands Group in the Indian Ocean – can be seen as monuments to 19th century British-style colonization, though their early paths to development took very different courses. Their transition to the status of external territories of the Australian Commonwealth in the 20th century – early in the case of Norfolk and later in the cases of Christmas and Cocos – put them on a common path in which serious tensions emerged between local populations which sought autonomous governance and the Commonwealth government which wanted to impose governmental systems similar to those applying to mainstream Australians. This article explores the issues involved, and seeks to relate the governmental history of the three island territories to the exploration of island jurisdictions developed in island studies research.